Does only the age of the hen matter in Salmonella enterica contamination of eggs?. (February 2019) - Crabb, Helen Kathleen; Gilkerson, James Rudkin; Browning, Glenn Francis
Abstract: Contamination of eggs with Salmonella enterica is a significant risk factor contributing to foodborne disease. Periods of peak egg contamination were identified by conducting longitudinal environmental and egg sampling in 7 layer flocks until they were 50 weeks of age. A total of 714 environmental samples and 8958 eggs were cultured using standard methods for the detection of salmonellae. Pooled egg contamination with Salmonella Typhimurium or Salmonella Infantis was detected at a true prevalence (TP) of 0.002 (95% CI = 0.001, 0.004) or 0.005 (95% CI = 0.004, 0.007), respectively. S. Typhimurium and S. Infantis were detected in individual egg components; in shell rinse at a TP of 0.014 (95% CI = 0.005, 0.038), in shell and membrane at a TP of 0.01 (95% CI = 0.003, 0.032), and in albumen and yolk content at a TP of 0.007 (95% CI = 0.001, 0.027). The concentration of salmonellae in all fractions was <1 CFU/mL. The TP of Salmonella enterica in eggs was highest at the onset of lay. Higher egg prevalence was associated with a lower body weight, higher egg production, higher egg weight and mass than the breed standard for age, and poorer feed conversion efficiency. Flock physiology appears to have an important influence on the detection of eggs contaminated with Salmonella enterica . Highlights: The true prevalence of Salmonella spp. in eggs was highest at the onset of lay. S. Typhimurium and S. Infantis were detected in the internal egg content (yolk and albumen) at a true prevalence of 0.007 (95% CI: 0.001, 0.027). Environmental contamination with Salmonella did not affect the true prevalence of the same salmonellae in eggs. Higher egg prevalence was associated with a lower body weight, higher egg production and egg weight than the breed standard.